PENGARUH SUBSTITUSI DEDAK HALUS DENGAN TEPUNG KULIT KOPI DALAM RANSUM TERHADAP PERFORMA BROILER - Murib, Sandro; Najoan, M.; Bagau, Betty; Untu, Ivone M (ZOOTEC, 2016)
ABSTRACT THE EFFECTS OF SUBSTITUTION OF  RICE BRAN AND COFFEE HULL MEAL IN RATION ON BROILER PERFORMANCE The effects of looking for alternative feed to variate feed ingredients for ration formulation is steel on going. The utilization of agricultural waste products are not maximized yet, although its availability are abundant, one of these agricultural waste products is coffee hull. The research evaluation the effects of rice bran and coffee hull meal in ration on broiler performances has been conducted at Faculty of Animal Science Unsrat Manado for six weeks using 60 broiler strain CP 707. Completely Randomized Design with 4 treatments and 5 replication was used. The treatments  were : R0 = substitution of rice bran   (0%) or ration with  21 % rice bran + 0% coffee hulls ; R1 = substitution of rice bran   (33.33%)or ration with 14 % or ration with +  7% coffee hulls; R2 =  substitution of rice bran   (66.66%) or ration with  7  % +   14 % coffee huls; R3 =  substitution of rice bran   (100 %)  or ration with0 % rice bran +   21 % coffee hulls. The results showed that there were significant, effects of treatments on feed consumption, body gain and feed conversion. Tukey test showed that the higher proportion of coffee hull meal the lower feed consumption and body gain, on the other land feed conversion of R3 significantly higher compared to  R0, R1and R3. Based on feed conversion it can be concluded that rice bran can be substituted by coffee hulls meal up to 66.66% or its utilization up to 14% in the broiler ration. Key words :Broiler, Rice Bran, Coffee Hull , Performance broiler.